The impact of historical redlining policies on community composition and the COVID-19 pandemic in Boston - Nicole B. Alkhouri; Victoria Fisher; Isaacson Michel; Caitlin O’Connor; Nadia N. Abuelezam (PLoS ONE, 2025)
The COVID-19 pandemic has accentuated racial and socioeconomic disparities that have existed in the U.S. because of structural racism. We aimed to understand how the legacy of historical redlining policies was associated with COVID-19 incidence in Boston ZIP code tabulation areas (ZCTAs) from March 2020 to December 2022. Data were extracted from the Institute for Social Research at the University of Michigan, the Boston Public Health Commission, the Boston Planning & Development Agency, and the American Community Survey. We ran a generalized linear model accounting for time to explore the association between historical redlining, characterized as Homeowners’ Loan Corporation (HOLC) grade, and monthly COVID-19 incidence rate. Models were adjusted for the proportion of the ZCTA population identified as non-White, were older than 75, homeowners, and foreign-born. We also accounted for the median household value in each ZCTA. We found no significant association between HOLC grade and monthly COVID-19 incidence rate in Boston (IRR: 0.95; 95% CI: 0.80, 1.12). Downstream effects of redlining, such as gentrification and higher median home value, were associated with a higher monthly COVID-19 incidence (IRR: 1.12; 95% CI: 1.01, 1.25). These results highlight the unique ways Boston’s historical racist policies have manifested themselves in health outcomes today. Place-based context and history is important when examining redlining in public health research.